Acessibilidade de pessoas com deficiência física e sensorial em unidades de saúde da família - Martins, Kaisy Pereira (2015)
Introduction: People with disabilities have physical and / or sensory that are closely related to accessibility issues. Therefore, it is necessary to ensure these individuals the effective exercise of citizenship and social life by the right to freedom and independence to come and go. Objective: To analyze the accessibility of people with physical and / or sensory impairment in the Family Health Units. Methodology: This is a descriptive exploratory research with a quantitative approach, performed in 90 buildings that make up the health units of the family in the city of João Pessoa - Paraiba. The data, which were collected during the months from March to May 2014, through a structured instrument developed from the Brazilian Standard 9050 of the Brazilian Technical Standards Association, were compiled and analyzed with the aid of the Statistical Package for the Social sciences version 20.0. Performed a descriptive analysis of the data and the association test, with statistically significant variable when p <0.05. Results: There was a lack of accessibility in almost all items analyzed in the units. Among them, who presented with a statistically significant association in relation to the physical structure on the way home / health institution were: no crosswalk (85.6%); curb kneeling at strategic points (65.6%); signs indicating the route to the institution (98.9%); lights fitted with pushbuttons (96.7%) and buzzer (100.0%); private parking for people with disabilities (97.8%); Access International symbol (SIA) on inputs and outputs (100.0%); obstacle free route of the parking spot to the entrance of the institution (81.1%) and signals with sound information on emergency exits or escape routes (100.0%). With regard to internal areas of health institutions, the results showed that 56.7% of the units where there are ramps, only 30.0% have maximum slope to minimize the efforts person with disabilities; in 32.2%, the floor is non-slip, and 2.2% the finish is differentiated at the beginning and end of the ramp to guide people with visual impairments. Concerning the securities and sanitation facilities in 100.0% of them there are no text information written in Braille; 60.0% do not have adequate toilets for people with disabilities, and 92.2% are not properly signed by the SIA. Conclusion: Urge the relentless pursuit to enhance accessibility for people with disabilities because it recognized that public policies and institutions do not meet this emerging need brings out the need to reform this care and reorganize the health services.